Elucidation of the electrochemical oxidation pathway of ammonia in dimethylformamide and the room temperature ionic liquid, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide - Buzzeo, M; Giovanelli, D; Lawrence, N; Hardacre, C; Seddon, K; Compton, R (2004)
The direct electrochemical oxidation of ammonia has been examined in both the organic solvent dimethylformamide (DMF) and the room temperature ionic liquid 1-ethyl-3- methylimidazolium bis(trifluoromethylsulfonyl)imide [EMIM][N(Tf)2]. The corresponding voltammetric responses have been shown to be similar in each solvent with a broad oxidative wave occurring upon the introduction of ammonia to the solution and the appearance of a new reductive wave following the oxidation. The oxidative reaction process has been examined and a suitable reaction pathway has been deduced, corresponding to the formation of ammonium cations after oxidation of the ammonia. A linear response of limiting current against vol% ammonia was observed in both DMF and [EMIM][N(Tf)2], suggesting potential application for analytical methods.